Influence of Photosynthetically Active Radiation on Grain Density of Rice - Venkateswarlu, B.; Vergara, B.S.; Visperas, R.M. (Wiley, 1987)
Increasing the number of high density (HD) grains can increase the grain yield of rice (Oryza sativa L.). Studies were conducted on the effect of different levels of photosynthetically active radiation (PAR) on the density of grains. ‘IR36’ was grown throughout its life cycle at 195, 390, and 780 μmol m−2 s−1 in the growth cabinets of the phototron. There was an increased production of spikelets and HD grains (specific gravity >1.20) as PAR increased. The low density (LD) grains also increased as PAR increased. When plants grown previously under natural light were exposed to different PAR after anthesis, the HD grains increased at higher PAR, while the LD grains decreased as PAR increased. The percentage contribution of HD grains to total grain yield emerged as a major determinant of grain yield; thus, cultivars possessing a higher proportion of HD grains would be advantageous even under low PAR. Individual grain weights were higher when plants were exposed to higher PAR after anthesis. The weight of individual grains showed a widerange at lower specific gravities (1.16 to 1.20) than at higher specific gravities (> 1.20). Spikelet and grain number per hill showed high positive correlation with shoot weight per hill. High density grains had a positive but lower correlation with shoot weight, indicating a possible limitation in production or transport of assimilates as HD grains were not realized in all the filled spikelets regardless of PAR level. High PAR from flowering to harvest can greatly increase the number of HD grains, which contributes to higher grain yield.